The geography of artificial levees in the United States - Knox, Richard Leo, author; Wohl, Ellen, advisor; Morrison, Ryan, advisor; Laituri, Melinda, committee member; Rathburn, Sara, committee member (Colorado State University. Libraries, 2022)
Connectivity between different parts of the landscape is an important theme for river ecosystem functions. Recent advances in conceptual models of river ecosystems, computing power, and data availability, resolution, and extent have allowed the exploration of this theme at continental and global scales. However, these studies have not included the impacts of artificial levees on floodplain function and extent due to the lack of complete artificial levee databases. Local and regional studies have explored the harmful effects and identification of artificial levees. Several characteristics of artificial levees have inhibited the extension of these studies to greater spatial scales (e.g., artificial levees are shaped like other natural and anthropogenic features; artificial levee height and width are small compared to the vertical and horizontal resolution and accuracy of earth observation data available at continental and global scales; artificial levees have a long history of construction). I first present a methodology and data set for the identification of artificial levees in a case study of seven basins (ranging in size from 1,700 to 8,000 square km each) in the continental United States (CONUS) and then apply the methodology to the entire CONUS. This methodology, which includes a model that only uses land cover, distance from stream flow, and basin variables, detected over 182,000 km of artificial levees. Next, I use this dataset in combination with a pre-existing artificial levee database to determine how artificial levees influence floodplain extent, land cover, and association with stream order size in the CONUS. Surprisingly, this revealed that the 100-year CONUS floodplain was of greater extent with artificial levees than if they were not constructed. And not surprisingly, the 8,100 square km of CONUS floodplain that are disconnected by artificial levees are predominantly cultivated or developed land cover. Finally, I conduct a critical review of floodplain functions and analyze case studies of floodplain restoration involving the alteration of artificial levees. I define five interconnected floodplain functions that are vital to river ecosystems and are adversely impacted by artificial levee construction. Studies that analyze floodplain restoration are heavily concentrated in North America and Europe and evaluate effects within 30 years of restoration. In the United States, this type of restoration impacts less than 1% of river kilometers with artificial levees and 1-2% of disconnected floodplains. This dissertation provides an important advance in understanding the impacts of artificial levees on floodplain extent and function at a large spatial scale. It also provides several avenues for continued research.
Keywords: biogeochemistry; floodplain functions; hydrogeomorphic floodplains; connectivity; biodiversity; floodplain restoration